Introduction. (Velvet Light Trap: A Critical Journal of Film & Television)
An introduction to the journal is presented in which the editors discuss various articles published within the issue on topics including the use of comedy in Internet videos, the use of the laugh track in the production of television comedies, and the history of women in American comedic films.